The Nucleocapsid Protein of Coronavirus Mouse Hepatitis Virus Interacts with the Cellular Heterogeneous Nuclear Ribonucleoprotein A1 in Vitro and in Vivo - Wang, Yicheng (Virology, 1999)
The nucleocapsid (N) protein of mouse hepatitis virus (MHV) and the cellular heterogeneous nuclear ribonucleoprotein A1 (hnRNP-A1) are RNA-binding proteins, binding to the leader RNA and the intergenic sequence of MHV negative-strand template RNAs, respectively. Previous studies have suggested a role for both N and hnRNP-A1 proteins in MHV RNA synthesis. However, it is not known whether the two proteins can interact with each other. Here we employed a series of methods to determine their interactions both in vitro and in vivo. Both N and hnRNP-A1 genes were cloned and expressed in Escherichia coli as glutathione S-transferase (GST) fusion proteins, and their interactions were determined with a GST-binding assay. Results showed that N protein directly and specifically interacted with hnRNP-A1 in vitro. To dissect the protein-binding domain on the N protein, 15 deletion constructs were made by PCR and expressed as GST fusion proteins. Two hnRNP-A1-binding sites were identified on N protein: site A is located at amino acids 1 to 292 and site B at amino acids 392 to 455. In addition, we found that N protein interacted with itself and that the self-interacting domain coincided with site A but not with site B. Using a fluorescence double-staining technique, we showed that N protein colocalized with hnRNP-A1 in the cytoplasm, particularly in the perinuclear region, of MHV-infected cells, where viral RNA replication/transcription occurs. The N protein and hnRNP-A1 were coimmunoprecipitated from the lysates of MHV-infected cells either by an N- or by an hnRNP-A1-specific monoclonal antibody, indicating a physical interaction between N and hnRNP-A1 proteins. Furthermore, using the yeast two-hybrid system, we showed that N protein interacted with hnRNP-A1 in vivo. These results thus establish that MHV N protein interacts with hnRNP-A1 both in vitro and in vivo.